A critical interrogation of the relation between the ecosystem approach and ecosystem services. Issue 2 (23rd January 2018) - De Lucia, Vito
Abstract : This article offers a critical interrogation of the relationship between two emerging conceptual frameworks whose importance has grown quickly within the context of international environmental law: the ecosystem approach and ecosystem services. Both premised on the concept of the ecosystem, their origin is parallel, but their present and future is convergent and increasingly intertwined. The ecosystem approach, increasingly deployed in a variety of normative and regulatory contexts, has become a key strategy for the integrated management of human activities, and has been characterized as a paradigm shift in environmental law and governance. Ecosystem services, mainstreamed by the Millennium Ecosystem Assessment series in the early 2000s, refer to the benefits people obtain from ecosystems. The relationship between the two concepts is arguably underexplored. This article aims at filling this gap from a particular critical legal perspective, and will read this relationship in terms of a 'biopolitical entanglement'.